2014
DOI: 10.5937/nbp1401141m
|View full text |Cite
|
Sign up to set email alerts
|

The crime scene in theoretical reflections on crime

Abstract: Sаžetak: Poslednjih decenija sve više do izražaja dolaze teorijski pristupi u čijem fokusu se nalazi geoprostor (mesto) na kojem dolazi do interakcije izvršioca i žrtve (mete) prilikom izvršenja krivičnog dela. Ovim pristupima je zajedničko interesovanje ka razumevanju načina na koji geoprostor "oblikuje" kriminalnu aktivnost. Oni teže da istraže kako okruženje utiče na stvaranje prilike i donošenje odluke kod učinioca da se izvrši krivično delo, odnosno pokušavaju da objasne obrasce ponašanja učinioca i žrtve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Thus there are works in the literature which refer to the existence of specific strategies for direct approach to a child, as well as strategies that provide for the offender to be left alone with an unsupervised child. 22 However, it is worth mentioning that many clinical and forensic oriented authors find that before committing a specific criminal offence the offenders found themselves in a seemingly favourable situations on several occasions, but they did not use it. Additionally, the evaluation of favourability first refers to isolation, i.e.…”
Section: Some Implications Of Phenomenological Characteristics Of Chimentioning
confidence: 99%
“…Thus there are works in the literature which refer to the existence of specific strategies for direct approach to a child, as well as strategies that provide for the offender to be left alone with an unsupervised child. 22 However, it is worth mentioning that many clinical and forensic oriented authors find that before committing a specific criminal offence the offenders found themselves in a seemingly favourable situations on several occasions, but they did not use it. Additionally, the evaluation of favourability first refers to isolation, i.e.…”
Section: Some Implications Of Phenomenological Characteristics Of Chimentioning
confidence: 99%